2020
DOI: 10.2174/0929867326666190326111851
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine and Diabetic Nephropathy

Abstract: Diabetic Nephropathy (DN) is a major complication in patients with type 1 or type 2 diabetes and represents the leading cause of end-stage renal disease. Novel therapeutic approaches are warranted. In view of a polymorphism in the carnosinase 1 gene CNDP1, resulting in reduced carnosine degradation activity and a significant DN risk reduction, carnosine (β-alanyl-L-histidine) has gained attention as a potential therapeutic target. Carnosine has anti-inflammatory, antioxidant, anti-glycation and reactive carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 94 publications
1
20
1
Order By: Relevance
“…Several studies could demonstrate that carnosine and anserine have specific dipeptide functions such as antioxidant activity [14,28] which cannot be explained by their corresponding amino acids alone. For example, treatment with carnosine or anserine prevented alterations of renal function in diabetic (db/db) mice [29][30][31]. Additionally, for proline-containing dipeptides the biological activities seem to be not only based on the free amino acid alone [1]; for Tyr-containing dipeptides [32] an inhibitory effect on ACE activity has been demonstrated, and Tyr-Asp improves plant tolerance to oxidative stress by directly interfering with glucose metabolism [33].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies could demonstrate that carnosine and anserine have specific dipeptide functions such as antioxidant activity [14,28] which cannot be explained by their corresponding amino acids alone. For example, treatment with carnosine or anserine prevented alterations of renal function in diabetic (db/db) mice [29][30][31]. Additionally, for proline-containing dipeptides the biological activities seem to be not only based on the free amino acid alone [1]; for Tyr-containing dipeptides [32] an inhibitory effect on ACE activity has been demonstrated, and Tyr-Asp improves plant tolerance to oxidative stress by directly interfering with glucose metabolism [33].…”
Section: Discussionmentioning
confidence: 99%
“…Carnosine scavenges carbonyls [ 6 , 7 ], inhibits glycation [ 8 ], prevents AGE formation and has antioxidant actions. Supplementation of carnosine in diabetic rodents increases renal carnosine concentrations [ 32 ] and consistently preserves renal morphology and function [ 20 ]. In humans carnosinemia, due to CN1 deficiency may be a non-disease; whereas accumulation of carnosine should protect against long-term sequelae of reactive metabolites accumulating, e.g., in diabetes and chronic renal failure [ 3 , 20 ] and may prevent cancer development [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of carnosine in diabetic rodents increases renal carnosine concentrations [ 32 ] and consistently preserves renal morphology and function [ 20 ]. In humans carnosinemia, due to CN1 deficiency may be a non-disease; whereas accumulation of carnosine should protect against long-term sequelae of reactive metabolites accumulating, e.g., in diabetes and chronic renal failure [ 3 , 20 ] and may prevent cancer development [ 33 ]. Efficacy of therapeutic carnosine supplementation in humans, however, is limited by a highly active serum CN1 largely preventing major increases in serum carnosine concentrations [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elbarbary NS et al reported that carnosine could reduce urine alpha-1 microglobulin, which is a urine biomarker of glomerular and tubular injury among diabetic patients, as well as urinary TGF-β [12]. Several studies in animal models also demonstrated antiin ammatory, anti-oxidant, antiglycation, antiproteinuric and vasculoprotective effects of carnosine [13,14].…”
Section: Discussionmentioning
confidence: 99%